СӨЗ БОСТАНДЫҒЫ ҚҰҚЫҒЫ ТУРАЛЫ ИДЕЯЛАРДЫҢ ҚАЛЫПТАСУЫ (Journal of actual problems of jurisprudence, 2019)
This article addresses questions about the development of ideas about freedom of speech and thought.